Transforming legal education In the era of fourth industrial revolution (IR4.0) - Amirnuddin, Puteri Sofia; Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (The Malaysian Current Law Journal Sdn Bhd, 2020)
The recent technological advances trigger the emergence of the Fourth IndustryRevolution (IR4.0) which is very dynamic and progressive to the extent most of themajor industries in the world have no option left but to transform the industryaccordingly in order to adapt to the changes in the IR4.0 era. Hence, this articleaims at exploring how the legal education offered at higher learning institutes canbe transformed to be in line with the IR4.0 in an efficient manner but withoutcompromising the quality. Tertiary education system should catch up with thisprogress to ensure that modern legal education would be fully modified andconcurrent with it. Currently, there is a significant delay in transforming legaleducational services offered at universities, colleges and other higher learninginstitutes with regard to fields of study, subjects offered, teaching and assessmentmethods, among others. Despite the fact that it is complex, for the time being, totransform the legal education to be in line with the IR4.0, it will benefit the societyunprecedentedly for a long run as it is the ‘game changer’ of this era.